The identity of the Organization in the Face of Change. The Case of Employees of Com.Tu.Lab when They Become Faculty Members at the National University of the Northeast (UNNE), Argentina. - Ernesto Daniel Ferrando; Sergio David Valenzuela; Nilce Marianela Sánchez (European Scientific Journal, ESJ, 2017)
We analyze processes of identification and symbolic appropriation of the institutional culture in the Labour Relations, Social Communication and Tourism Careers in a state university which until 2008 functioned unified as an institute called Dependent Careers of the Chancellorship. After the mentioned date and until 2013, each was formally transferred - although not geographically - to the Faculties of Economic Sciences, Humanities and Arts Design and Cs. Of Culture respectively, thus in 2012, a General Coordination to contain and manage them is created. Since the carers continue to function in the same space and former employees, the aim of this research is to determine whether the old dominant administrative practices persist or they were modified given the transition to change. The methodology employed consisted in the techniques of semi-structured interviews supported by the participant observance of the employees in their everyday tasks. A loss of the sense of autonomy was detected on them, showing a permanent necessity of building a new identity while living in conflict with the residual. The formality and the hierarchy are part of the university culture. The recommendations would be to plan the on-going formation on the mission, vision and functions of the new public office.